Asuhan Keperawatan Pada Pasien Dengan Hipertensi Diruangan Interne Rsud Prof. H. M. Yamin, S. H Pariaman - Adek Wulan Safitri; Kheniva Diah Anggita; Linda Marni; Aulia Asman (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hypertension is often dubbed the "silent killer" as it is frequently asymptomatic yet carries a high risk of serious complications such as heart disease, stroke, and kidney failure. According to the WHO (2025), hypertension is the leading cause of premature death worldwide, with an estimated 1.4 billion adults suffering from the condition. Based on the 2023 Indonesian Health Survey (SKI), the prevalence of hypertension in Indonesia reached 30.8% among residents aged >18 years, while in West Sumatra, it was recorded at 25.16%. In Pariaman City (2024), there were 8,164 hypertension patients who received health services. Medical record data at Prof. H. M. Yamin, S.H. Hospital, Pariaman, showed that hypertension patients experiencing complications reached 99.01% (602 patients) of the total cases in 2025.The purpose of this case study is to provide comprehensive nursing care for Mrs. E with hypertension in the Internal Medicine Ward of Prof. H. M. Yamin, S.H. Hospital, Pariaman. The method used is a descriptive case study conducted over five days, from February 4th to 9th, 2026, involving one research subject.The results of the initial assessment revealed extreme blood pressure of 210/117 mmHg and a pain scale of 7. Based on data analysis, four nursing problems were established: acute pain, risk of ineffective cerebral perfusion, disturbed sleep patterns, and risk of nutritional deficits, with acute pain as the top priority. The evaluation over five days showed that all nursing problems were resolved, marked by a decrease in blood pressure to 165/97 mmHg, the disappearance of pain (scale 0), and improved sleep patterns and nutritional intake, allowing the patient to be discharged. It is expected that the patient and their family will ensure that they adhere to a healthy lifestyle, a low-salt diet, and regular health checks to prevent complications.